Presence of allelic loss and PTEN mutations in malignant gliomas from Malay patients - Zainuddin, Norafiza; Jaafar, Hasnan; Isa, Mohd. Nizam; Abdullah, Jafri Malin (Malaysian Medical Associations, 2004)
Loss of heterozygosity (LOH) on several loci and mutations on PTEN tumor suppressor gene (10q23.3) occur frequently in sporadic gliomas. We have performed polymerase chain reaction (PCR)-LOH analysis using microsatellite markers and single-stranded conformational polymorphism (SSCP) analysis to determine the incidence of allelic losses on chromosome 10q, 9p, 17p and 13q and mutations of exons 5, 6 and 8 of the PTEN gene in malignant gliomas. Twelve of 23 (52.2%) malignant glioma cases showed allelic losses whereas 7 of 23 (30.4%) samples showed aberrant band patterns and mutations of the PTEN gene. Four of these cases showed LOH on 10q23 and mutations of the PTEN gene. The data on LOH indicated the involvement of different genes in gliomagenesis whereas mutations of the PTEN gene indicated the role of PTEN tumor suppressor gene in the progression of glioma in Malay population.